Neutrophil Extracellular Traps Promote Angiogenesis: Evidence From Vascular Pathology in Pulmonary Hypertension. Issue 10 (October 2016) - Aldabbous, Lulwah; Abdul-Salam, Vahitha; McKinnon, Tom; Duluc, Lucie; Pepke-Zaba, Joanna; Southwood, Mark; Ainscough, Alexander J.; Hadinnapola, Charaka; Wilkins, Martin R.; Toshner, Mark; Wojciak-Stothard, Beata
Abstract : Objective—: Inflammation and dysregulated angiogenesis are features of endothelial dysfunction in pulmonary hypertension. Neutrophil extracellular traps (NETs), produced by dying neutrophils, contribute to pathogenesis of numerous vascular disorders but their role in pulmonary hypertension has not been studied. We sought evidence of (NETs) formation in pulmonary hypertension and investigated the effect of NETs on endothelial function. Approach and Results—: Plasma and lung tissues of patients with pulmonary hypertension were analyzed for NET markers. The effects of NETs on endothelial function were studied in vitro and in vivo. Patients with chronic thromboembolic pulmonary hypertension and idiopathic pulmonary hypertension showed elevated plasma levels of DNA, neutrophil elastase, and myeloperoxidase. NET-forming neutrophils and extensive areas of NETosis were found in the occlusive plexiform lesions and vascularized intrapulmonary thrombi. NETs induced nuclear factor κB–dependent endothelial angiogenesis in vitro and increased vascularization of matrigel plugs in vivo. Angiogenic responses were associated with increased release of matrix metalloproteinase-9, heparin-binding epidermal growth factor–like growth factor, latency-associated peptide of the transforming growth factor β1, and urokinase-type plasminogen activator, accompanied by increased endothelial permeability and cell motility. NETs-induced responses depended on myeloperoxidase/H2 O2 -dependent activation of Toll-like receptor 4/nuclear factor κB signaling. NETs stimulated the release of endothelin-1 in HPAECs (human pulmonary artery endothelial cells) and stimulated pulmonary smooth muscle cell proliferation in vitro. Conclusions—: We are the first to implicate NETs in angiogenesis and provide a functional link between NETs and inflammatory angiogenesis in vitro and in vivo. We demonstrate the potential pathological relevance of this in 2 diseases of disordered vascular homeostasis, pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension. Abstract : Supplemental Digital Content is available in the text.